Does the textbook matter? Longitudinal effects of textbook choice on primary school students' achievement in mathematics. (December 2018) - van den Ham, Ann-Katrin; Heinze, Aiso
Highlights: Textbooks have a substantial impact on mathematics achievement in primary school. Textbooks notably differ in their effects on student achievement. Longitudinal effects of textbooks on student achievement seem to be cumulative. Textbooks might be a relevant covariate when analyzing intervention effects. Abstract: Mathematics textbooks are ascribed an important role for classroom practice. Until now there are still open questions concerning the genuine effect of textbooks on students' learning in mathematics. This paper examines the effect of different textbooks representing the same curriculum on the student achievement by reanalyzing a longitudinal data set on primary school students' mathematics skills from Grade 1 to 3 (N = 1664). Results from multilevel regression analyses showed that mathematics teachers' textbook choice has a substantial effect on the students' mathematics achievement and that individual textbooks substantially differ in their effects. Furthermore, there are indications that the effect of textbook choice is cumulative over the school years. The findings suggest that textbooks should be considered as an important covariate in educational research and that textbook choice is a relevant factor for educational practice.